2021
DOI: 10.1177/17562848211020285
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of Clostridioides difficile infection and inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is a chronic disease of the intestinal tract that commonly presents with diarrhea. Clostridioides difficile infection (CDI) is one of the most common complications associated with IBD that lead to flare-ups of underlying IBD. The pathophysiology of CDI includes perturbations of the gut microbiota, which makes IBD a risk factor due to the gut microbial alterations that occur in IBD, predisposing patients CDI even in the absence of antibiotics. Superimposed CDI not only worsens I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In our study, an extremely high percentage of COVID-19 patients received broad-spectrum of antibiotics prior to and during their hospital stay. Similar percentages have been reported by Sehgal et al and Khanna et al in the first half of 2021 [32,33]. Azithromycin was the most frequently prescribed antibiotic for outpatient treatment of COVID-19 as empirical coverage for possible superinfection of the respiratory tract and thus, independently associated with the risk of developing CDI.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, an extremely high percentage of COVID-19 patients received broad-spectrum of antibiotics prior to and during their hospital stay. Similar percentages have been reported by Sehgal et al and Khanna et al in the first half of 2021 [32,33]. Azithromycin was the most frequently prescribed antibiotic for outpatient treatment of COVID-19 as empirical coverage for possible superinfection of the respiratory tract and thus, independently associated with the risk of developing CDI.…”
Section: Discussionsupporting
confidence: 83%
“…Performing stool microbiology on specimens obtained from IBD patients in a flare-up, a study demonstrated that 10.5% of these relapses were associated with intestinal infections, half of them (and the most abundant one) being CDI [22]. In addition, recent evidence further supports the fact that CDI is the most common complication in IBD patients, leading to a flare-up [25][26][27].…”
Section: Risk Factors For Developing and For Severity Of CDI In Patie...mentioning
confidence: 99%
“…A tapered and pulsed vancomycin regimen, vancomycin in standard dosage 10 days followed by rifaximin 400 mg TID for 20 days, fidaxomicin 200 mg BID for 10 days, and vancomicin or fidaxomicin followed by fecal microbiota transplantation (FMT), represent therapeutic choices in recurrent infection [ 24 , 123 ]. Data supporting the efficacy of prolonged oral vancomycin therapy in IBD result from a study performed by Lei et al, who found lower rates of CDI recurrence as a result of long-duration therapy (21–42 days), comparing with short-duration vancomycin therapy (10–14 days) [ 124 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%